Mid-Holocene skua remains from King George Island, Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; Montalti, Diego; del Valle, Rodolfo Augusto (Paläontologische Zeitschrift)
Seven avian remains from Mid-Holocene strata of the south-eastern coast of Potter Peninsula (King George Island: Isla 25 de Mayo, South Shetland Islands, Antarctica) are reported. They were described and assigned to the Brown Skua Stercorarius antarcticus lonnbergi (Aves, Laridae), a living species currently breeding in the area. The presence of penguins in the same sequence is in agreement with the current dynamics of the coastal ecosystems of Antarctica. Nowadays, penguins and skuas frequent these same environments. Aus dem mittleren Holoza¨n der su¨do¨stlichen Ku¨ste der Potter-Halbinsel (King George Island: Isla 25 de Mayo, South Shetland Islands, Antarktis) werden sieben Rippen beschrieben, die dem Braunen Skua Stercorarius antarcticus lonnbergi (Aves, Laridae) zugeordnet werden. Diese Art kommt auch heute noch in der Region vor. Das gemeinsame Vorkommen von Pinguinen in der selben Fundschicht steht im Einklang mit der derzeitigen Dynamik der O¨ kosysteme der antarktischen Ku¨sten. Heute leben auch noch Pinguine und Raubmo¨wen in derselben Umgebungen. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Montalti, Diego. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: del Valle, Rodolfo Augusto. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina